2018
DOI: 10.3390/toxics6040062
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity Assessment of Iron Oxide (Fe3O4) Nanoparticles on Physical and Biochemical Quality of Rainbow Trout Spermatozoon

Abstract: The aim of this study was to evaluate the in vitro effect of different doses (50, 100, 200, 400, and 800 mg/L) of Fe3O4 nanoparticles (NPs) at 4 °C for 24 h on the kinematics of rainbow trout (Oncorhynchus mykiss, Walbaum, 1792) spermatozoon. Firstly, Fe3O4 NPs were prepared at about 30 nm from Iron (III) chloride, Iron (II) chloride, and NH3 via a co-precipitation synthesis technique. Then, the prepared Fe3O4 NPs were characterized by different instrumental techniques for their chemical structure, purity, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…This is in agreement with previous reports, that suggest a hypothesis that the time of interaction between semen and NPs can be crucial regarding their potential toxic activity [ 34 , 35 ]. In accordance with this scientific hypothesis, a significant decrease of VCL, VSL and VAP was observed after a prolonged (24 h) incubation of rainbow trout semen with Fe 3 O 4 NPs [ 24 ].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This is in agreement with previous reports, that suggest a hypothesis that the time of interaction between semen and NPs can be crucial regarding their potential toxic activity [ 34 , 35 ]. In accordance with this scientific hypothesis, a significant decrease of VCL, VSL and VAP was observed after a prolonged (24 h) incubation of rainbow trout semen with Fe 3 O 4 NPs [ 24 ].…”
Section: Discussionmentioning
confidence: 60%
“…Despite the potential biological benefits of NPs, nanotoxicity and its impact on cells’ health is a concern [ 14 ]. Previous studies reported that Fe 3 O 4 NPs affect rainbow trout sperm [ 24 ], whilst titanium dioxide TiO 2 NPs negatively affect mouse gene expression of Leydig cells, as well as semen quality parameters [ 25 ]. No studies were found to report the effects of Fe 3 O 4 NPs on boar semen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study done by Huang et al (2019) showed that exposure to γ-Fe2O3 NPs leads to increased embryonic developmental toxicity in larval zebrafish and mice (possibly related to mitochondrial dysfunction and oxidative stress), while α-Fe2O3 and Fe3O4 have no such effects. On the other hand, a recent study by Özgür et al (2018) also revealed that, in Oncorhynchus mykiss spermatozoon, Fe₃O₄ nanoparticles lead to significant changes in oxidative status followed by the increase of the levels of total glutathione and malondialdehyde. The limited number of studies and often conflicting results stress the importance of future research in this field.…”
Section: Discussionmentioning
confidence: 96%
“…Weissleder et al [18] studied the toxic effect on rats and beagle dogs, revealing that no toxicity was detected in animals that received 3000 mmol Fe/kg overall. Furthermore, various materials, such as silane-based compounds, metals, polymers, and fatty and amino acids, have been used for coating and stabilizing the surface of iron oxide NPs in order to reduce toxicity and increase biocompatibility [19,20,21]. Among other materials, silane-based compounds are most promising since they have high biocompatibility, stability, low toxicity, low cost, and high prospects for functionality [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%